Optimizing diabetes cupping point from graph colouring perspective - Aziz, Nur Atikah; Yusof, Yuhani; Mohd Radzuan, Hazulin; Noviantri, Viska (Semarak Ilmu Publishing, 2024)
Nowadays, diabetes has become one of the most common chronic diseases that lead to mortality around the world. Managing diabetics patients require multidisciplinary approach, in which the patient must maintain a healthy lifestyle, take specific medications for recuperation, and receive specialized medical care. However, apart from conventional medication that are being prescribed nowadays, the ancient therapy of cupping can help in the healing process and provide benefits for diabetes. Medicinal cupping is a specific technique that involves applying cups to specific points on the body to stimulate healing and improve health. Each disease possesses distinct locations that require cupping and practise. The practitioner will apply the cups randomly or based on the patient’s complaint, which will have an impact to the cost of therapy. In addition, no mathematical method has been done previously to ensure that this practical procedure is optimized. This paper proposes a graph model to identify the optimal number of cupping points for diabetes using a graph colouring approach based on the perspective of human nerves.